2011
DOI: 10.1016/j.yqres.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Importance of sampling across an assemblage of glacial landforms for interpreting cosmogenic ages of deglaciation

Abstract: Deglaciation chronologies for some sectors of former ice sheets are relatively poorly constrained because of the paucity of features or materials traditionally used to constrain the timing of deglaciation. In areas without good deglaciation varve chronologies and/or without widespread occurrence of material that indicates the start of earliest organic radiocarbon accumulations suitable for radiocarbon dating, typically only general patterns and chronologies of deglaciation have been deduced. However, mid-latit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 67 publications
(104 reference statements)
3
14
0
1
Order By: Relevance
“…Rinterknecht et al, 2006;Balco and Schaefer, 2006;Stroeven et al, 2010Stroeven et al, , 2011, but dating of more extensive pre-LGM glaciations has been applied to the north-eastern FIS (Linge et al, 2006), the northern Cordilleran Ice Sheet (Ward et al, 2007;Stroeven et al, 2014) and the Patagonia Ice Sheet (Kaplan et al, 2007;Darvill et al, in press). …”
Section: Cosmogenic Datingmentioning
confidence: 99%
“…Rinterknecht et al, 2006;Balco and Schaefer, 2006;Stroeven et al, 2010Stroeven et al, , 2011, but dating of more extensive pre-LGM glaciations has been applied to the north-eastern FIS (Linge et al, 2006), the northern Cordilleran Ice Sheet (Ward et al, 2007;Stroeven et al, 2014) and the Patagonia Ice Sheet (Kaplan et al, 2007;Darvill et al, in press). …”
Section: Cosmogenic Datingmentioning
confidence: 99%
“…The existing SIS chronology for the Holocene is based largely on the varve records from Sweden and Finland from the Baltic Sea/Ice Lake [ Cato , 1985; Fromm , 1985], several minimum‐limiting radiocarbon dates on bulk organic matter and macrofossils from northern Sweden [ Andersen , 1981; Karlen , 1979], and cosmogenic radionuclide dates from northern Sweden [ Stroeven et al , 2011]. The oldest macrofossil radiocarbon date on wood from northern Sweden places deglaciation of this region ice‐free before 9.5 ± 0.2 ka (8.48 ± 0.16 14 C ka BP, ST‐4507) [ Karlen , 1979].…”
Section: Holocene Ice Sheet Retreat and Sea Level Risementioning
confidence: 99%
“…Two to three metres of rock thickness is often considered to be sufficient for this (e.g. Balco, ; Stroeven et al ., ), although Braucher et al . () reported measurable concentrations of 36 Cl, 10 Be and 26 Al at depths of up to 11 m below the surface.…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…Two to three metres of rock thickness is often considered to be sufficient for this (e.g. Balco, 2011;Stroeven et al, 2011), although Braucher et al (2011 reported measurable concentrations of 36 Cl, 10 Be and 26 Al at depths of up to 11 m below the surface. Where insufficient rock thickness is removed, by glacial erosion for example, the resulting bedrock surface will retain isotopes acquired during the pre-glacial phase of subaerial exposure and when analysed will yield anomalously 'old' exposure ages.…”
Section: Isotope Inheritancementioning
confidence: 99%